2020
DOI: 10.1021/acs.jmedchem.9b01409
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Activity Studies of Disulfide-Deficient Analogues of αO-Conotoxin GeXIVA

Abstract: αO-conotoxin GeXIVA from Conus generalis is a potent antagonist of the α9α10 nAChR and analgesic in animal models of pain. This peptide has two disulfide bond cross-links, and the bead and ribbon isomers have similar inhibitory activity against α9α10 nAChRs. We synthesized 12 disulfide-deficient analogues of bead GeXIVA, and all remained potent inhibitors of α9α10 nAChR. The most potent disulfide-deficient analogue displayed IC 50 values of 6 and 33 nM at rat and human α9α10 nAChRs, respectively, representing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 74 publications
0
14
1
Order By: Relevance
“…672 Disulfide-deficient analogues of α-conotoxin GeXIVA retain some measure of α9α10 nAChR antagonistic activities, with NMR and molecular dynamics simulations suggesting the disulfide bonds and peptide termini do interact with the receptor and that the central segment of residues 12 to 18 can form a stable α-helical conformation that binds to the receptor. 673 Further study of α-conotoxin RgIA, also an α9α10 nAChR antagonist, has identified that Arg 7 in the first disulfide loop is important for overall potency, while changes in the second loop can fine-tune selectivity towards the human, vs. rat, α9α10 nAChR subtype. 674 Of a series of four N- to C-termini-linked variants of the globular isomer of α-conotoxin TxIB ( C. textile ) one was identified as exhibiting retained α6β2* nAChR activity with improved serum stability.…”
Section: Molluscsmentioning
confidence: 99%
“…672 Disulfide-deficient analogues of α-conotoxin GeXIVA retain some measure of α9α10 nAChR antagonistic activities, with NMR and molecular dynamics simulations suggesting the disulfide bonds and peptide termini do interact with the receptor and that the central segment of residues 12 to 18 can form a stable α-helical conformation that binds to the receptor. 673 Further study of α-conotoxin RgIA, also an α9α10 nAChR antagonist, has identified that Arg 7 in the first disulfide loop is important for overall potency, while changes in the second loop can fine-tune selectivity towards the human, vs. rat, α9α10 nAChR subtype. 674 Of a series of four N- to C-termini-linked variants of the globular isomer of α-conotoxin TxIB ( C. textile ) one was identified as exhibiting retained α6β2* nAChR activity with improved serum stability.…”
Section: Molluscsmentioning
confidence: 99%
“…Disulfide bond-containing peptides have attracted attention as drugs for treating various diseases. Furthermore, numerous disulfide-containing peptides have been evaluated under trials and have been crucial in the recent development of small molecule drugs. The disulfide bond is an important structural motif that can stabilize a peptide’s second structure, increasing the biological and pharmaceutical activities of the molecule. Prior to the synthesis of the disulfide bonds, the dicysteine-containing peptide chains were initially constructed on a resin and were subsequently cleaved from the resin by a cleavage cocktail. Following the precipitation of peptides from the cleavage solution, the peptides were purified prior to use.…”
Section: Introductionmentioning
confidence: 99%
“…A possible medicinal chemistry approach could be to focus on several known peptide toxins. For example, disulfide-deficient analogues of the αO-Conotoxin GeXIVA display higher affinity for α2β2 nAChRs compared to α7 and α3β4, although the comparison with α4β2 is still not available [136]. Unfortunately, from our perspective, most previous medicinal chemistry studies have focused on α7 receptors, because of their possible implication in neurodegenerative diseases [135].…”
Section: Steps Toward Precision Medicine In Adshementioning
confidence: 99%